أثر استخدام طريقة المناقشة في تدريس الفيزياء على تحصيل طلبة السنة الثانية من التعليم المتوسط في مدينة الجزائر - العاطف, أحمد; شنوقه, عبد المجيد; بوجانة, عاشور (Sciences humaines, 2014)
هدفت هذه الدراسة إلى معرفة أثر استخدام طريقة المناقشة في تدريس الفيزياء على تحصيل طلبة السنة الثانية من التعليم المتوسط في القبةـ بمدينة الجزائر وسط، مقارنة بالطريقة التقليدية، للعام الدراسي 2006 ـ 2007. تكون مجتمع البحث من طلبة السنة الثانية متوسط، والبالغ عددهم 920 طالبا وطالبة، وبلغت عينة البحث التي اختيرت عشوائيا 80 طالبا وطالبة (40 إناث، 40 ذكور)، قسمت إلى مجموعتين، إحداهما تجريبية وعدد أفرادها 42 (22 إناث، 20ذكور)، درست بطريقة المناقشة، والثانية ضابطة وعدد أفرادها 38 (18 إناث، 20 ذكور)، تعلمت بالطريقة التقليدية   The objective of this research is to evaluate the impact of the discussion method in physics teaching compared to traditional way.     The used sample involves students of the second year of the middle school education from Kouba city (Algiers center) in the 2006/2007 academic year. The population of research consisted of 920 students (males, females). The used research sample, which constituted by 80 students (40 males and 40 females), is randomly chosen. This sample divided in two groups. The experimental group, constituted by 42 students (22females,20males), and the test group, which is constituted by 38 students (18 females, 20 males). The experimental group students studied via the discussion method, but the students of the test group studied via the traditional method of teaching.